Pembelajaran Teks Anekdote Bermuatan Karakter Dan Berwawasan Lingkungan Dengan Pendekatan Berbasis Teks ( Studi Kasus Pada Smk Roudlotul Mubtadiin Balekambang Jepara) - Miftakhussalam Miftakhussalam (Departement of Mathematics Education, 2023)
This research aims to describe the structure, type, textual and contextual meaning of anecdotal texts containing character and environmental insight; anecdotes as a medium for conveying communication containing character and local wisdom; and the suitability of anecdotal texts containing character and local wisdom as Indonesian language teaching materials at Roudlotul Mubtadiin Balekambang Jepara Vocational School. This type of research is descriptive qualitative. The research data is in the form of anecdotal text containing character and an environmental perspective that has been validated by experts. The result of this research is an anecdote text containing character. Meanwhile, local wisdom values ​​include the values ​​of compassion, wisdom, a strong personality, humility, and sociability. The contextual meaning of anecdotal texts containing character and environmental insight includes situations, events, speech acts and speech functions that reflect the character and environmental insight of Indonesian society. Anecdotes are very appropriate to use in conveying character and environmental insight. Anecdotal texts resulting from research are suitable as Indonesian language teaching materials at Roudlotul Mubtadiin Balekambang Jepara Vocational School